2020
DOI: 10.1101/2020.05.05.077875
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Planarian stem cells sense the identity of missing tissues to launch targeted regeneration

Abstract: In order to regenerate tissues successfully, stem cells must first detect injuries and then produce missing cell types through largely unknown mechanisms. Planarian flatworms have an extensive stem cell population responsible for regenerating any organ after amputation. Here, we compare stem cell responses to different injuries by amputation of a single organ, the pharynx, or removal of tissues from other organs by decapitation. We find that planarian stem cells adopt distinct behaviors depending on what tissu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 96 publications
(152 reference statements)
0
1
0
Order By: Relevance
“…In the highly regenerative planarian flatworm, ERK phosphorylation is one of the first responses to injury, detectable 15 min after cutting 7 . ERK signaling has been argued to be important in planaria for overall regeneration 7 , to play a role in allowing differentiation 6 , to activate stem cell subpopulations 8 and to play a headspecific role 9 . Several studies have shown that ERK inhibition immediately following amputation leads to the formation of headless animals 6,7,9 .…”
Section: Introductionmentioning
confidence: 99%
“…In the highly regenerative planarian flatworm, ERK phosphorylation is one of the first responses to injury, detectable 15 min after cutting 7 . ERK signaling has been argued to be important in planaria for overall regeneration 7 , to play a role in allowing differentiation 6 , to activate stem cell subpopulations 8 and to play a headspecific role 9 . Several studies have shown that ERK inhibition immediately following amputation leads to the formation of headless animals 6,7,9 .…”
Section: Introductionmentioning
confidence: 99%